Relationship Between Serum Zinc Concentration with Post-partum Depression among Women in Coastal Area of Indonesia - Indriasari, R.; Kurniati, Y.; Syam, A.; Syamsuddin, S.; Mansur, M.A; Amir, S. (Pakistan Journal of Nutrition, 2019)
Background and Objective: Women in coastal area have limited access to nutritious diet and vulnerable to micronutrient deficiencies, including zinc. Zinc deficiency is believed to play an important role in the development of mood disorders such as post-partum depression. Therefore, we aimed to determine the relationship between serum zinc concentration and post-partum depression among women in coastal area of Indonesia. Materials and Methods: Edinburgh Postnatal Depression Score (EDPS) was administered to 87 post-partum women to determine the post-partum depression symptoms. Serum zinc was measured with ELISA method using Bio Assay Quanti Chrome Zinc Assay Kit (DIZN-250). Data was analyzed using chi-square and Pearson correlation test. Results: Results showed that 35.5% of mothers experienced post-partum depression symptoms and 57.4% of mothers had very low serum zinc. There was no significant relationship between serum zinc level and postpartum depression (p = 0.729). Moreover, Pearson correlation test shows a weak correlation between serum zinc concentration and EPDS score ® = -0.063, p = 0.564). Although not significant and weak, this inverse correlation indicated that as the serum zinc concentration increased the EPDS score decreased. Conclusion: There was no significant relationship between serum zinc level and postpartum depression, however, high percentage of women with post-partum depression symptoms and zinc deficiency implies that more attentions should be placed to post-partum women’s mental health and zinc status.